L’invention du biome Cerrado - Catherine Aubertin; Florence Pinton (Confins)
What is at stake in this paper is an understanding of how the Cerrado, a previously unknown territory, then dedicated to intensive farming, was promoted at the beginning of the 2000s as a biome and an issue for environmental concerns. Its projection on the international stage during the Conference of Copenhagen on Climate Change in 2009 thereafter contributed to turn this vaguely delimited territory into an international issue for climate change and struggle against deforestation, with the affirmation of two opposite trends: an agribusiness converted to green technologies and the implementation of areas of socio-biodiversity. The construction of the biome is analysed by putting into perspective the Amazon. The authors consider that the two regions are inextricably united in their destiny. Specific geopolitical and scientific contexts and insertion in different stages in the history of sustainable development may explain the contrasting views of these areas. At the time of its qualification as a remarkable biome, the Cerrado is already endowed with the comprehensive kit of scientific, economical and legal tools, demonstrating the evolution of representation on biodiversity.